Role of biological therapy for inflammatory bowel disease in developing countries. Issue 5 (13th October 2011) - Rogler, Gerhard; Bernstein, Charles N; Sood, Ajit; Goh, Khean Lee; Yamamoto-Furusho, Jesús K; Abbas, Zaigham; Fried, Michael
Abstract : Inflammatory bowel disease (IBD) has become a global disease. Its incidence in developing countries is rising. In Asia, this has been attributed to the rapid modernisation and westernisation of the population. As IBD emerges in developing nations, there is a need to reconcile the most appropriate treatment for these patient populations from the perspectives of both disease presentation and cost. In the West, biological agents are the fastest-growing segment of the prescription drug market. They typically cost several thousand to several tens of thousands of dollars per patient per year. The healthcare systems in developing countries will struggle to afford such expensive treatments. Developing countries cover two-thirds of the earth's surface and are home to 3–5 billion inhabitants, constituting three-quarters of all humanity. If IBD emerges to the same extent in those countries as it has in the West, the need for biological therapy will increase dramatically, and the pharmaceutical industry, healthcare providers, patient advocate groups, governments and non-governmental organisations will have to discuss how to handle this. The authors propose that this dialogue should begin now with regard to (1) the major needs of patients with complicated IBD in developing countries, (2) the potential need for biological therapy in developing countries to treat IBD, (3) the necessary infrastructure for selecting patients with IBD who need biological therapy, and (4) medical/ethical issues limiting the use of biological therapy.